Israel's beneficent dead - Schmidt, B (1992)
﻿ This investigation aims to ascertain whether or not the Israelites believed in the supernatural beneficent power of the dead. First, a lexicon of selected mortuary practices and beliefs is outlined. In the Israelite context, those rites most likely to reflect this belief are necromancy and those which fall within the purview of the ancestor cult intended to express veneration or worship of the ancestors (ch. 1). Secondly, an evaluation of the relevant texts from Syria-Palestine of the third to first millennia B.C.E. demonstrates that a longstanding West Semitic or Canaanite origin for Israel's belief in the supernatural beneficent power of the dead cannot be established on the basis of these data (chs. 2 and 3). Thirdly, an examination of the Hebrew Bible demonstrates that while a concern to care for or commemorate the dead might be inferred, neither an ancestor cult nor ancestor veneration or worship in particular can be established on the basis of the available literary (or material) evidence. Moreover, while necromancy is occasionally attested, the relevant passages which polemicize against Israel's embrace of this practice originate either in the last days of the Judahite monarchy or, more likely, during the exile itself. The historical reality which gave rise to this polemical tradition was the threat which Mesopotamian religion and magic beginning with the Neo-Assyrian period posed to later (dtr?) Yahwism (ch. 4). Comparative ethnographic data suggests that the longstanding absence of the belief in the beneficent dead in Israel and Syria-Palestine might be partially explained as a reaction to the pervasive fear of the dead. Nevertheless, once this belief was embraced by late Israelite society, owing to contemporary developments in politics (Mesopotamian hegemony), economics (depletion of resources), and religion (popularity of divination), necromancy, not ancestor veneration or worship, presented itself as the preferred ritual expression of this belief (conclusion).